Experiments with Cestrum laevigatum Schecht. In laboratory animals - Barros, Glênio Cavalcanti de; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
Experiments were made in mice, rats, guinea-pigs, and rabbits with buds and young leaves of Cestrum laevigatum. The fresh green or dried plant material was given to the animals in the ration or by a stomach tube, in powder form, as juice or as water extract. Only the rabbit showed symptoms of poisoning and two animals died after having received a 11% water extract of the dried plant in the proportion of 14 g/kg of animal weight, which corresponds to about 70 g/kg of fresh green plant material. Guinea-pigs tolerated doses ten times as high as the lethal dose for rabbits. Mice consumed unharmed doses which were fatal to rabbits. Histopathological examination of organs of the poisoned rabbits revealed centrilobular liver distrophy.